PERKEMBANGAN MORFOLOGI KAWASAN CAGAR BUDAYA DARMO SURABAYA TAHUN 1905-1943 - Muhammad Ilham Perkasa; Bambang Soemardiono; Happy Ratna Santosa (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: Surabaya City has undergone rapid development characterized by changes in its physical form. A renowned Darmo heritage landscape has been experiencing such things. But none of the research had uncovered the morphological development of Darmo historic landscape. Even if, Darmo is a historic residential area and became the only masterwork in Surabaya by Henri Maclaine Pont, a renowned Dutch architect. Thus, the purpose of this study is to understand the Darmo Area further from the perspective of the area wholeness used in the urban morphological study by identifying the historical stages of morphological development. The strategy used is historical-interpretative which involves data collection methods of archival studies, literature studies, and in-depth interviews with experts. Meanwhile, the method of analysis used is historical diachronic analysis. The results of the study seemingly suggest that the Darmo Area has three major morphological stages, namely the pre and planning period, the development period, and extension. It shows the generative process of the area, and this can be the basis for historic urban landscape management. Hence, these morphological elements should be conserved altogether as urban morphology entities to ensure the unity of the Darmo historic landscape.Abstrak: Kota Surabaya telah mengalami perkembangan yang pesat, ditandai dengan perubahan bentuk fisiknya. Yang menjadi perhatian, kawasan cagar budaya Darmo mengalami hal tersebut. Namun belum ada penelitian yang mengungkap perkembangan morfologi kawasan bersejarah Darmo. Padahal, Darmo merupakan kawasan hunian bersejarah dan menjadi satu-satunya karya di Surabaya oleh Henri Maclaine Pont, seorang arsitek ternama Belanda. Dengan demikian, tujuan dari penelitian ini adalah memahami Kawasan Darmo lebih jauh dari perspektif keutuhan kawasan yang digunakan dalam studi morfologi perkotaan dengan mengidentifikasi tahapan sejarah perkembangan morfologi. Strategi yang digunakan adalah sejarah-interpretatif yang melibatkan metode pengumpulan data studi kearsipan, studi literatur, observasi, dan wawancara mendalam dengan para ahli. Sedangkan metode analisis yang digunakan adalah analisis sejarah diakronik. Hasil kajian menunjukkan bahwa Kawasan Darmo memiliki tiga tahapan sejarah besar, yaitu periode praperencanaan dan perencanaan, periode pengembangan, dan perluasan. Terlihat proses generatif kawasan dan hal ini dapat menjadi dasar pengelolaan kawasan cagar budaya. Oleh karena itu, elemen-elemen morfologi harus dilestarikan bersama sebagai kesatuan morfologi perkotaan untuk menjamin kesatuan Kawasan Darmo.